Ca alors ! 2 - Vallantin, Philippe; Griffiths, James; Nicholson, John; Sedunary, MIchael; Papadima-Sophocleous, Salomi (My University, 2000)
The journey of discovery and adventure continues as students enter the linguistically and culturally rich world of Ça alors ! 2. Set in France and in other pays francophones, Ça alors ! 2 consolidates and extends the language introduced in the first level and broadens the cultural context. The Ça alors! 2 Workbook Workbook is an indispensable companion to the full colour Textbook. It features a wide range of listening, reading, grammar and writing exercises as well as extension activities (including some computer-based activities), all aimed at the multi-level classroom of today. The listening comprehension exercises presented in the Workbook can be heard on the Ça alors! 2 Audio CD Pack.
Keywords: French language; Textbook for foreign speakers